Designing a Regional Teacher Professional Development Enterprise - Kinser-Traut, Jennifer Y.; Marx, Ronald W. (Frontiers in Education, 2022)
Teacher professional learning is foundational to high quality P-12 education. While many researchers have identified the importance and criteria of high-quality professional learning, little research explains how this professional learning can be implemented in a regional system. This ten-month case study offers one planning approach to engage important stakeholders, including principals, other education leaders, professional development providers and especially teachers, in a process to design a regional professional learning collaborative. This approach employed features of high-quality professional development throughout the planning activities. Drawing on principals from design thinking, findings identify the importance of the empathize, define, ideate, and prototype phases in designing innovative systems for professional learning. Emphasis is placed on the importance of shared authority with teachers, optimism inherent to design thinking, and relationship and community building throughout these phases. Implications for the development of educator professional learning systems are discussed and a coda sharing the current efforts of the collaborative is presented.